1984
DOI: 10.2466/pr0.1984.55.3.779
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward AIDS, Herpes II, and Toxic Shock Syndrome

Abstract: The purposes of this study were to determine by questionnaire current attitudes about AIDS, herpes, and Toxic Shock Syndrome and to what extent concern about these diseases affected behavior of 232 volunteers from classes in a midwestern university. The majority of the respondents expressed relatively little concern about any of these diseases. Except for a few respondents who expressed extreme concern, there were also no changes in current self-reported rates of sexual activity compared to a year ago. Male ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(13 citation statements)
references
References 2 publications
1
11
0
1
Order By: Relevance
“…Straits, Alivia, Haskinst, & Rutherford, 1989;DiClemente, Zorn, & Temoshok, 1986;McDermott. Hawkins, Moore, & Cittandino, 1987;Sherr, 1987;Simkins & Eberhage, 1984;and Temoshok, Sweet, & Zich, 1987). It was anticipated that negative unfounded stereotypes about AIDS would be inversely related to the use of direct, confrontative attempts to discuss AIDS with a potential sexual partner.…”
Section: Measuring Aids-related Discussion Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Straits, Alivia, Haskinst, & Rutherford, 1989;DiClemente, Zorn, & Temoshok, 1986;McDermott. Hawkins, Moore, & Cittandino, 1987;Sherr, 1987;Simkins & Eberhage, 1984;and Temoshok, Sweet, & Zich, 1987). It was anticipated that negative unfounded stereotypes about AIDS would be inversely related to the use of direct, confrontative attempts to discuss AIDS with a potential sexual partner.…”
Section: Measuring Aids-related Discussion Strategiesmentioning
confidence: 99%
“…DiClemente et al, 1986;DiClemente et al, 1989;McDermott et al, 1987;Sherr, 1987;Simkins & Eberhage, 1984;and Temoshok et al, 1987). Research participants who reported that they would use rational tactics to persuade a close partner to discuss AIDS expressed less close-minded beliefs about AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have considered attitudes toward AIDS (Bajos & Marquet, 2000;Clift et al, 1990;Crawford, 1990;Prochaska et al, 1992;Simkins & Eberhage, 1984), and toward condoms (Akande, 1994;Chapman et al, 1992;Dolcini et al, 1995;Kesby, 2000;Madlala, 1997;Ross, 1988;Siegel et al, 1994;Thompson et al, 1997;Winter & Goldy, 1993), attitudes to AIDS precautions in general have received scant attention. Moore and Barling (1991) showed such attitudes to be multidimensional rather than merely pro-or anti-precautionary behavior.…”
Section: The Present Studymentioning
confidence: 97%
“…Quelques recherches s'intéressent aux différences d'attitudes des soignants à l'égard de patients atteints de différentes maladies chroniques (Katz et al, 1987;Kelly et al, 1988;Simkins et Eberhage, 1984;Simkins et Kushner, 1986;Triplet et Sugarman, 1987). Les recherches de Katz et al (1987) et de Kelly et al (1988) montrent que le personnel infirmier réagit plus négativement à un patient atteint du SIDA que de cancer.…”
Section: Attitudes Et Comportements à L'égard Des Personnes Atteintesunclassified